A pilot study of integrating standardized patients in problem-based learning tutorial in Taiwan. Issue 6 (June 2019) - Chang, Ching-Chih; Lirng, Jiing-Feng; Wang, Pei-Ning; Wang, Shuu-Jiun; Chen, Chen-Huan; Yang, Ling-Yu; Huang, William J; Huang, Hui-Chun
Abstract : Background: Problem-based learning (PBL) has been widely adopted in medical education; however, its application has been questioned due to the lack of interaction with a real patient. Standardized patients (SPs) might solve this problem. Herein, we tested the impact of integrating SPs in a PBL tutorial. Methods: In 2017, a total of 313 students, 66 facilitators, and 36 SPs were enrolled at National Yang-Ming University, Taiwan. The SPs presented the symptoms/signs of the cases then the students interviewed them to obtain the detail history. All students, facilitators, and SPs were invited to complete the questionnaires before and after this program. Results: Most SPs considered that both the second-year dental medical student and third-year medical students participated actively and were competent enough but students and facilitators considered that the fourth-year medical students might be more prepared. Overall, the students thought highly of the interactions with the SPs. Only about one-fifth felt that this design caused unnecessary pressure among the students and facilitators. They agreed that this program significantly inspired the student's learning motivation (pre- vs post-course: 4.1 ± 0.7 vs 4.3 ± 0.7, p < 0.001), increased their confidence level in interviewing patients (4.0 ± 0.8 vs 4.2 ± 0.7, p < 0.001), and encouraging critical thinking (4.0 ± 0.7 vs 4.2 ± 0.7, p < 0.001). Conclusion: The SPs, facilitators, and students had different viewpoints with regards to integrating SPs in the PBL tutorial. However, a majority agreed that this design enhanced the motivation of students and supported such an application in PBL tutorials.